NILAI-NILAI PENDIDIKAN ISLAM DALAM TAFSIR AYAT JIHAD (Studi atas Tafsir Fi Zhilal Al-Qur`an Karya Sayyid Quthb) - Suheri Sahputra Rangkuti (POTENSIA: Jurnal Kependidikan Islam, 2018)
This article contains the discourse on the values of Islamic education in the verses of the jihad verse by Sayyid Quthb. The word jihad which has the basic meaning of seriousness to fight something, certainly does not have to be in the form of a battle. In this discourse many educational values were found that needed to be outlined and at the same time explained that the verses of jihad in the interpretation of Sayyid Quthb were interpreted without emotional and radical elements. This article consists of three parts; first, describe the impact of the radical understanding of jihad on Islamic education. Dialogue on the epistemology of Islamic education values. Second, it contains a touch of Sayyid Quthb's interpretation of the verse of Jihad and describes the values of Islamic education contained in it. Third, it contains conclusions that reflect all parts of this article.